Optimization of 2200 WP Solar Power Components for EV Charging Using SMART Method - Nopriyanti, Rani; Setiawan, Heri; Harianton, Iwan; Adi Seotopo, Antonius; Sadiyo, M; Nugroho, Dimas; Nur Iman, Ryan; Sanhaji, Ganis (Spektrum Industri, 2026)
The performance, efficiency, and lifetime of off-grid photovoltaic (PV) systems are strongly influenced by the appropriate selection of key components, including solar panels, charge controllers, batteries, and inverters. This study aims to determine the optimal configuration of a 2200 Wp off-grid PV system for an electric vehicle charging station at Bandung Polytechnic of Manufacturing (Polman Bandung). A Decision Support System based on the Simple Multi-Attribute Rating Technique (SMART) was employed to evaluate multiple technical and functional criteria across several component alternatives. A total of 8 alternatives, consisting of 2 alternatives for each component, were quantitatively assessed using weighted criteria and preference scores to obtain a final ranking. The results indicate that the optimal configuration consists of monocrystalline solar panels, an MPPT charge controller, LiFePO4 batteries, and a pure sine wave inverter, achieving the highest overall utility value. The system produced an output of approximately 1300 W, corresponding to about 59% of the installed capacity (2200 Wp), which reflects the system performance ratio under real operating conditions rather than the intrinsic efficiency of the PV modules. This study contributes to the selection of appropriate components that significantly improve the efficiency, reliability, and operational performance of the system. In conclusion, the SMART-based DSS effectively identifies the optimal components for a 2200 Wp off-grid solar power system, providing a practical and robust solution for electric vehicle charging under varying environmental conditions while ensuring improved efficiency, reliability, and system lifetime.